Analisis Umur Simpan Bubuk Kakao dalam Kemasan Plastik Standing Pounch Menggunakan Pendekatan Model Arrhenius - Iman Sabarisman; Satria Bhirawa Anoraga; Ika Restu Revulaningtyas (Jurnal Nasional Teknologi Terapan (JNTT), 2017)
Cocoa powder is usually used to be a raw material in the chocolate products. In the large scale production, cocoa powder must be stored at specific time period before it was used. The quality of cocoa powder can decrease during storage period hence shelf life analysis of cocoa powder is needed. The aim of this study was to determine the shelf life of cocoa powder by Accelerated Shelf Life Testing (ASLT) Method with Arrhenius Model Approach. Cocoa powder was stored at different temperature (30, 40, and 50oC) and different packaging type (plastic with zipper and paper craft with zipper) to simul atedacceleration of damage as a result of temperature increase. Cocoa powder contained high level of fat so it more easily gone rancid. Moisture content and peroxide value were observed periodically that shown the quality parameters of cocoa powder. Initial moisture content and fat content of cocoa powder were analyzed by gravimetric method. Degree of rancidity which was shown with peroxide value was analyzed by iodometric titration method. According to the change of peroxide value, the shelf life of cocoa powder can be estimated.